PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. FARINDA BERSAUDARA DI DESA JAMBUK KECAMATAN BONGAN KABUPATEN KUTAI BARAT - Aprillia Tiansih Sulistio (JURNAL AGRIMENT, 2020)
This research is motivated by the implementation of corporate social responsibility (CSR) for companies to society and the benefits of implementing CSR for the community. Corporate social responsibility (CSR) in a nutshell can be defined as corporate social responsibility to its stakeholders. Companies that implement CSR will benefit, namely maintaining and boosting the reputation and brand image of the company, can improve relations with stakeholders, improve relations with the government, increase employee morale and productivity and get the opportunity to get awards. The company cannot release its responsibility for both the environment and the surrounding community. If the company still wants sustainability, it must pay attention to both the community and the environment. The purpose of this research is to identify the implementation of CSR by PT. Farinda Bersaudara and identification of benefits received by the community from social, economic and environmental aspects by PT. Farinda Bersaudara. The results of this study indicate that the community's assessment of the company regarding the CSR program on average from the total score of the respondents' answers is 83.44, meaning that most respondents stated that the implementation of CSR at PT. Farinda brothers are good. CSR implementation at PT. Farinda Bersaudara only covers 1 aspect, namely social aspects, for example, such as financial assistance for the 17 August event, religious holidays and also the company providing assistance in the form of buses for school children around the company